Sustainability of Duck Farming Business in Indramayu Regency: MDS Analysis Approach - Nuralfiyani, Amelia; Firman, Achmad; Herlina, Linda (Universitas Galuh, 2025)
This study aims to analyse the level of sustainability of duck farming in Indramayu District by considering environmental, economic and social impacts. In addition, this study also focuses on identifying and understanding the factors that hinder the sustainability of the business, assessing the influence of technology use and institutional support, and knowing the strategic steps that can be taken to improve the sustainability of duck farming. The research method used is quantitative method. The research was conducted in Sliyeg and Sindang sub-districts, in January to February, 2025, involving 96 participating respondents that are randomly selected. The analysis method used in this study is Multidimensional Scaling (MDS), which is applied to determine the sustainability status of duck farming. The results research showed that the level of sustainability of duck farming is still lacking, with varying sustainability index values in each dimension. Factors such as low technology adoption, financial constraints and limited access to training are the main challenges that need to be overcome. Institutional support and the application of modern technology are expected to improve production efficiency and business sustainability. The resulting strategic recommendations include enhancing farmers' access to training on modern duck farming practices, providing subsidized loans for infrastructure improvement, and facilitating partnerships with feed suppliers. For example, implementing regular government-led training programs in each sub-district could increase awareness and adoption of efficient feeding systems, while financial assistance can help farmers build better housing facilities.